Pendistribusian Zakat Melalui Program Kampung Zakat Mandiri Dalam Mendorong Ekonomi Warga RW 05 Kedungjaya Cirebon - siska mariawati; Atih Purwasih; Ipan Muhamad Fadilah; Jiada Yahya; Rahmatullah (Al Naqdu, 2023)
Zakat is one of the obligations of Muslims which has been stipulated in the Qur'an. Zakat is one of the pillars of Islam which is always mentioned parallel to prayer. Zakat rights are given to 8 ashnaf which have been described in the Qur'an. The distribution of zakat in addition to 8 ashnaf can also be managed in other forms such as the independent zakat village program. The Ministry of Religion (Kemenag) of the Republic of Indonesia has established zakat villages in a number of regions in Indonesia. Microeconomics is an economic subject that is economically rational, while Kampung Zakat is a program of the Ministry of Religion in collaboration with local governments and a number of zakat amil bodies (BAZ). With this program, a group of low-income people will be fostered and empowered based on zakat, infaq, and alms funds. Empowerment that will be accepted by the community includes the fields of economy, education, religious development, health, and social humanity. The village zakat program is an effort to alleviate poverty based on frontier, remote, and disadvantaged areas (3T) through optimizing zakat funds managed by BAZNAS and the amil zakat institution (LAZ). This program was initiated by the extension team of KUA Kedawung Cirebon Regency, in the village of Kedungjaya Blok Siledu as a pilot in the implementation of the independent zakat village program.